Inflation and employment in open economies : essays - Lindbeck, Assar (Amsterdam ; New York : North-Holland Pub. Co. ; New York : sole distributors for the U.S.A., and Canada, Elsevier North-Holland, 1979)
The purpose of this book is to present, in the form of twelve essays, some of the results of the work carried out in the field of macroeconomic theory and stabilization policies in highly open economies.
Includes bibliographical references and index.
osc 27/09/2017
Loans
Keywords: Unemployment; Foreign exchange rates